The secret life of romantic comedy - Deleyto, Celestino (Manchester University Press, 2019)
'The secret life of romantic comedy offers a new approach to one of the most popular and resilient genres in the history of Hollywood. Steering away from the rigidity and ideological determinism of traditional accounts of the genre, this book advocates a more flexible theory, which allows the student to explore the presence of the genre in unexpected places, extending the concept to encompass films that are not usually considered romantic comedies. Combining theory with detailed analyses of a selection of films, including To Be or Not to Be (1942), Rear Window (1954), Kiss Me Stupid (1964), Crimes and Misdemeanors (1989) and Before Sunset (2004), the book aims to provide a practical framework for the exploration of a key area of contemporary experience - intimate matters - through one of its most powerful filmic representations: the genre of romantic comedy. Original and entertaining, The secret life of romantic comedy is perfect for students and academics of film and film genre' --Back cover.
Made available via: manchesterhive.
Keywords: Romantic comedy films -- History and criticism.; Love in motion pictures.; Comédies romantiques (Films) -- Histoire et critique.; Amour au cinéma.; Film, TV and radio.; Film theory and criticism.; PERFORMING ARTS -- Film -- History & Criticism.; PERFORMING ARTS / Film / History & Criticism; Romantic comedy films; Love in motion pictures; The Arts -- Performing arts -- Films, cinema -- Film history, theory & criticism.; Electronic books; Criticism, interpretation, etc.